Cross-cultural adaptation of the scale National Emergency Department Overcrowding Score (NEDOCS) for use in Brazil - Henrique Meirelles Boldori; Rosane Mortari Ciconet; Karin Viegas; Rafaela Schaefer; Márcio Neres dos Santos
ABSTRACT Objective To describe the process of translation and cross-cultural adaptation of the National Emergency Department Overcrowding Score (NEDOCS) into the Portuguese language for use in Brazil. Method Methodological study of translation and cross-cultural adaptation into the Portuguese language of Brazil, founded in the recommendations of the Guidelines for the Process of Cross-Cultural Adaptation of Self-Report Measures, that comprise the stages of initial translation; synthesis of the translations; back-translation; committee of experts; pretesting and introduction of the scale to the author. Results The Portuguese-adapted scale presented semantic, idiomatic, experimental and conceptual equivalence with the original one; the total value of the Cronbach`s Alpha was -0,401 due to the non-positive intercorrelation among the scale items. Conclusions The NEDOCS scale has proved to be a reliable instrument to be utilized in the real-time monitoring of the assignment of emergency services. Thus, it contributes to the managerial and assistance processes besides providing health indicators.